Analysis and Improvement of the User Interface of the Project Plan Website in the Construction Division of PT Telkom Akses Tasikmalaya using Heuristic Evaluation - Ai Nuraiman; Suprih Widodo; Yuniar Bagas Yudha Rinda Pradana (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2026)
A well-designed user interface (UI) is crucial for the effectiveness of information delivery and user experience in organizational systems. Currently, the project planning website of the Construction Division at PT Telkom Akses Tasikmalaya faces issues related to a monotonous interface design and overly complex feature presentation. This study aims to analyze and improve the UI of the website. The method used is heuristic evaluation, focusing on interface simplification and design consistency. Data were collected through a questionnaire consisting of 10 questions based on heuristic principles, distributed to five evaluators representing employees of the construction division. The proposed design was evaluated using a severity rating scale. The evaluation results show an overall average score of 0.74. This value falls within the 0 to 1 scale range, indicating that the new interface does not present significant usability problems, or only superficial (minor) issues. These improvement recommendations significantly simplify feature complexity and enhance visual consistency, thereby improving interaction quality and the effectiveness of project information delivery to users.